Information vs the cyberspace domain. Issue 2 (4th May 2022) - Nakayama, Bryan James
ABSTRACT: Faced with ongoing large-scale cyber espionage and the rising prominence of information operations targeting social media, the cyber conflict scholarship has entered into a renewed debate over how to characterise the role and place of cyberspace conflict in broader patterns of international security. In response to these empirical challenges, this paper argues that the current scholarship is limited because it uses the 'cyberspace domain' – a doctrinal concept originating in the U.S. military – as a conceptual foundation. This paper argues that the cyberspace domain should be replaced with a holistic conception of "information competition" of which there are three paradigms: cyberspace domain, mixed, and information. All states seek to intervene in the flow and storage of information across domestic and international contexts; information competition is better able to capture information-related interactions between states and observed empirical variation in how states approach information technology and conflict. For example, China and Russia centre 'information' as the core organising framework for their approach to information technology and conflict. This paper also demonstrates how an information competition framework better clarifies the role that the U.S. has played in shaping Russian and Chinese approaches to information competition.